Performance Analysis of IEEE 802.15.6 Contention-based MAC Protocol - Ullah, Sana (2015)
IEEE International Conference on Communications (IEEE ICC 2015). 8 to 12, Jun, 2015, IEEE ICC 2015 - Communications QoS, Reliability and Modeling, London, United Kingdom.